The use of repetitive transcranial magnetic stimulation as an adjunct to constraint induced therapy - Henderson, Lenora, author; Malcolm, Matthew Paul, advisor; Greene, David, committee member; Davalos, Deana Beth, committee member (Colorado State University. Libraries, 2013)
Cerebral vascular accident (CVA) or stroke is a leading cause of disability in the United States. Hemiplegia is a common and persistent outcome of stroke and is present in 80 percent of stroke survivors. Upper extremity hemiplegia, in particular, tends to persist beyond functional recovery in other areas. Intensive training techniques, like constraint induced therapy (CIT) have been shown to significantly improve functioning of the upper extremity, months or even years post-CVA. Repetitive transcranial magnetic stimulation (rTMS) is a method of stimulating and augmenting the neurophysiology of the motor cortex in order to promote the neuroplastic changes that are associated with motor recovery. Like CIT, rTMS has demonstrated significant improvements in functional recovery of the upper extremity in stroke survivors. This study examined the potential benefits of using rTMS as an adjunctive treatment with CIT. Methods: 16 adult stroke survivors were randomized to either a CIT plus sham rTMS group (n = 8) or a CIT plus true rTMS group (n = 7). 1 participant was lost due to attrition. This is a double blind, sham controlled study. A two-way repeated measures ANOVA was used for analysis. Outcome Measures: TMS measures of MT, SICI, ICF, and recruitment curve. Functional measures were Wolf Motor Function Test (WMFT), Stroke Impact Scale (SIS), and Motor Activity Log- Quality of Movement (MAL-QOM). Results: Our neurophysiologic measures did not show significant differences between groups or over time for either group. Most of our functional measures showed significant differences over time for both groups, but not between groups. Conclusion: The small sample size, coupled with dropped data and high variability of data likely interfered with our ability to show significant differences between groups. However, 3 functional outcomes appeared to show a trend to a more sustained improvement at the 4 month follow-up assessment. These were Mal-QOM, SIS- strength and SIS- hand functioning. Further, a subset of rTMS responders may exist. These responders may have anatomical and physiological indicators that distinguish them from non-responders. We were not able to control for these difference in this study, but would recommend a deeper investigation into these potential differences for future rTMS studies.
Keywords: hemiperesis; TMS; stroke